Mechanisms of tumor-associated macrophages in breast cancer and treatment strategy - Jin, Hong; Meng, Xinyue; Feng, Jianwei (Frontiers in Immunology, 2025)
Breast cancer (BC) is the most common cancer in women and a leading cause of cancer-related mortality. Despite advances in screening and treatment, outcomes for advanced or recurrent BC remain poor, highlighting the need for new strategies. Recent research emphasizes the tumor microenvironment (TME), particularly tumor-associated macrophages (TAMs), as key drivers of tumor growth, metastasis, and resistance to therapy. The presence of M2-like TAMs in the TME promotes immune evasion and tumor progression across BC subtypes. This review summarizes TAMs classification, their role in BC, and emerging therapies targeting TAMs, including depletion, inhibition of recruitment, and reprogramming from pro-tumoral M2 to anti-tumoral M1 phenotypes. Targeting TAMs offers a promising strategy to improve BC treatment outcomes.